Her last breath : a novel - Adams, Taylor (William Morrow, an imprint of HarperCollins, 2026)
"After years of excuses, Tess has finally agreed to go caving with her best friend Allie. Their lives have diverged sharply since high school--Allie is a self-made travel influencer, while Tess is a shy (and claustrophobic) legal assistant struggling to pay for law school. Maybe she's a little jealous of Allie's globe-trotting life. Who wouldn't be? As Tess and Allie descend into the depths, they realize they're not alone. A stranger who claims to be a fellow caver harasses them. Confident, take-no-shit Allie insults the guy--and he retaliates. Soon, Tess is trapped inside a narrow crawl space hundreds of feet underground, fighting to stay alive. Twenty-four hours later, as a hospitalized Tess recounts her harrowing story of survival, the detective interviewing her shares new and shocking secrets about Allie's true past. Together, they begin to suspect the brutal attack wasn't so random after all. Who was Allie, really? Why did this man target them? And did Tess really leave the danger behind when she escaped the cave?"--Amazon.